The level of positive thinking among the first secondary graders / Science Branch (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims to investigate the level of positive thinking among the first secondary graders/ science branch, and to identify whether there are statistically significant differences in positive thinking attributed to the gender variable. The study sample consists of (195) male and female first secondary graders in Karak region who constitute 25% of the study population. The results reveal that the overall arithmetic mean of the positive thinking level among the first secondary graders/ science branchwas highly appreciated. The results also show that there were no statistically significant differences at the level of significance (≥α 0.05) in the level of positive thinking among thefirst secondary graders in Karak region, that was attributed to gender variable. The studyrecommends to develop the level of positive thinking among the first secondary graders/ science branch, and to establish educational and guidance seminars in order to improve the level of positive thinking among students. Also,  conduct similar studies and researchesinvestigating the level of positive thinking and its relationship to some variables among secondary school students.